Swelling of Steel Film by Hydrogen Absorption at Cathodic Potential in Electrolyte. Issue 6 (12th June 2020) - Garai, Debi; Carlomagno, Ilaria; Solokha, Vladyslav; Wilson, Axel; Meneghini, Carlo; Morawe, Christian; Murzin, Vadim; Gupta, Ajay; Zegenhagen, Jörg
Abstract : A 4‐nm‐thick alloy film with a metal composition close to AISI 304 stainless steel, deposited on a multilayer, was investigated by Jörg Zegenhagen and co‐workers (article number 2000055 ) as a model of the stainless‐steel surface region crucial for pitting corrosion. Using the X‐ray standing wave method, the oxidation states of iron, chrome and nickel as well as film composition and changes after electrolyte exposure are resolved depth‐selectively. Hydrogen loading by exposure to 0.1 M KCl at cathodic potential leads to swelling of the film by 11%, thus decreasing the resistance to pitting corrosion and finally leading to embrittlement.